Fluorescent nucleobase analogues for base–base FRET in nucleic acids: synthesis, photophysics and applications - Bood, Mattias; Sarangamath, Sangamesh; Wranne, Moa S.; Grøtli, Morten; Wilhelmsson, L. Marcus (Beilstein Journal of Organic Chemistry, 2018)
Förster resonance energy transfer (FRET) between a donor nucleobase analogue and an acceptor nucleobase analogue, base–base FRET, works as a spectroscopic ruler and protractor. With their firm stacking and ability to replace the natural nucleic acid bases inside the base-stack, base analogue donor and acceptor molecules complement external fluorophores like the Cy-, Alexa- and ATTO-dyes and enable detailed investigations of structure and dynamics of nucleic acid containing systems. The first base–base FRET pair, tCO–tCnitro, has recently been complemented with among others the adenine analogue FRET pair, qAN1–qAnitro, increasing the flexibility of the methodology. Here we present the design, synthesis, photophysical characterization and use of such base analogues. They enable a higher control of the FRET orientation factor, κ2, have a different distance window of opportunity than external fluorophores, and, thus, have the potential to facilitate better structure resolution. Netropsin DNA binding and the B-to-Z-DNA transition are examples of structure investigations that recently have been performed using base–base FRET and that are described here. Base–base FRET has been around for less than a decade, only in 2017 expanded beyond one FRET pair, and represents a highly promising structure and dynamics methodology for the field of nucleic acids. Here we bring up its advantages as well as disadvantages and touch upon potential future applications.
Keywords: B-to-Z-DNA transition; fluorescent base analogues; FRET; netropsin; nucleic acid structure and dynamics; quadracyclic adenines; tricyclic cytosines; Z-DNA